Efektivitas Program Makan Bergizi Gratis (MBG) dalam Meningkatkan Kehadiran Siswa Sekolah Dasar - Ering, Cherol Nelson; Lolaro, Gischella Elvira; Wuisang, Metty; Tendean, Angelia Friska (Fakultas Ilmu Keperawatan Universitas Klabat, 2026)
The Free Nutritious Meal Program (MBG) is an Indonesian government policy aimed at improving the nutritional status, health, and educational quality of elementary school students. Student attendance is one of the key indicators used to assess educational success. This study aimed to analyze the effect of the MBG program on student attendance at SD GMIM Kinilow. This study employed a quantitative approach with a one-group pre-test post-test design. The population consisted of all 227 students at SD GMIM Kinilow, with a sample of 125 students selected using stratified random sampling. Data were collected using student attendance observation sheets before and after the implementation of the MBG program. Data analysis was conducted using univariate and bivariate methods, with the Wilcoxon test applied at a 95% confidence level (p < 0.05). The results showed that prior to the implementation of the MBG program, most students were categorized as having low attendance (32.8%). After the program was implemented, the majority of students were categorized as having high attendance (72.8%). Statistical analysis indicated a significant difference in student attendance before and after the implementation of the MBG program (p value = 0.000 < 0.05). In conclusion, the MBG program has a significant effect on improving student attendance at SD GMIM Kinilow. It is expected that this program can be sustained and further developed as a strategy to support improvements in student health and school attendance at the elementary level. Program Makan Bergizi Gratis (MBG) merupakan kebijakan pemerintah Indonesia yang dirancang untuk meningkatkan status gizi, kesehatan, dan kualitas pendidikan siswa sekolah dasar. Kehadiran siswa di sekolah menjadi salah satu indikator penting dalam menilai keberhasilan pendidikan. Penelitian ini bertujuan untuk menganalisis pengaruh pelaksanaan MBG terhadap tingkat kehadiran siswa di SD GMIM Kinilow. Penelitian ini menggunakan pendekatan kuantitatif dengan desain one group pre-test post-test. Populasi penelitian mencakup seluruh siswa SD GMIM Kinilow sebanyak 227 orang, dengan sampel 125 siswa yang dipilih melalui teknik stratified random sampling. Pengumpulan data dilakukan menggunakan lembar observasi kehadiran siswa sebelum dan sesudah implementasi program MBG. Analisis data dilakukan secara univariat dan bivariat dengan uji Wilcoxon pada tingkat kepercayaan 95% (p < 0,05). Hasil penelitian menunjukkan bahwa sebelum pelaksanaan MBG, sebagian besar siswa memiliki tingkat kehadiran rendah (32,8%). Setelah program diterapkan, mayoritas siswa mengalami peningkatan kehadiran ke kategori tinggi (72,8%). Uji statistik menunjukkan adanya perbedaan yang signifikan antara tingkat kehadiran sebelum dan sesudah pelaksanaan MBG (p value = 0,000 < 0,05). Dengan demikian, dapat disimpulkan bahwa program MBG berpengaruh signifikan dalam meningkatkan tingkat kehadiran siswa di SD GMIM Kinilow. Program ini diharapkan dapat terus dilanjutkan dan dikembangkan sebagai strategi dalam mendukung peningkatan kesehatan serta partisipasi belajar siswa di sekolah dasar.